Diagnosing and Identifying Factors affecting the Prediction of Duration for Construction Projects Using Artificial Neural Network: Systematic Review - حميد عباس; فائق محمد سرحان الزويني (Latakia University Journal -Engineering Sciences Series, 2022)
The current study dealt with one of the most important problems that the construction projects suffer from, which is the deviation of the planned duration in the construction projects, as the deviation of the duration has become a critical issue facing this type of projects. The critical impact that affects the prediction of the duration of construction projects using artificial neural network in the past 25 years. In this context, the main objective of the study was to conduct a systematic review of the literature in the field of determining the most important critical factors affecting the estimation of the time periods of construction projects using the artificial neural network, according to the recognized scientific contexts in the field of systematic review, through a literature review. This dealt with this subject for the period extending from 1996 to 2021. For the purpose of achieving the objectives of the study, a systematic review was conducted based on the database (Google Scholar), (EBSCO) and (Research gate), and the study concluded that there are 236 influential factors in predicting the duration of construction projects. It was divided according to the main axes: residential projects and the most important factors influencing them (the efficiency of the project manager, support for senior management, the number of floors and the building area), infrastructure projects represented by roads, irrigation and drainage, and the most important factors are the following (the initial cost and length of the project, the number of intersections, and earthworks, Furniture, weather conditions, project size, and institutional and business projects represented by school buildings, and the most important factors are as follows (change orders and experience The supervising engineer, the duration of the contract, and the rank of the contracting company), in addition to the industrial projects represented by industrial buildings, the most important of which are (type of work, type of contract, capital and work location).